PEMBELAJARAN JARING-JARING MAKANAN SISWA KELAS V BERBASIS PROJECT BASED LEARNING BERBANTUAN MEDIA PIRAMIDA JARING-JARING MAKANAN - Laely Ayu Candra Sasqia; Panca Dewi Purwati (STKIP Subang, 2024)
Learning that still uses conventional learning models, where schools still apply scientific learning models and the use of learning media is still lacking so this study aims to (1) describe the application of Project-Based Learning based learning models assisted by Food Nets Pyramid media in class V Food Net Science subject matter, and (2) describe student learning outcomes based on the application of learning models Based on Project Based Learning assisted by Media Pyramid of Food Nets on the subject matter of Science Nets Food Webs class V. The research method used was qualitative descriptive with research subjects as many as 20 students. The participants of the study were grade V students of MI Nurul Huda who were involved in learning using the PjBL model assisted by the Food Net-Web Pyramid media. Data was collected through classroom observation, interviews, and document analysis. The results showed a significant increase in students' understanding and grades after the application of the PjBL model assisted by the Food Net-Web Pyramid media. This is shown by most students achieving and exceeding the Minimum Learning Completeness Criteria (KKTP). There was an increase in student learning outcomes from 53% of students whose scores were still below Minimum Learning Completeness Criteria to 17.6% and an increase in the average score from 66.47 to 83.53 which indicates the average score above Minimum Learning Completeness Criteria.